THU0026 Greater Diagnostic Delay in Early-Onset than in Late-Onset Systemic Lupus Erythematosus - Data from Reuma.Pt/Les. (10th June 2014) - Sousa, S.; Gonçalves, M.J.; Inês, L.; Duarte, C.; Fernandes, S.; Terroso, G.; Romão, V.C.; Cerqueira, M.; Raposo, A.; Couto, M.; Nero, P.; Novoa, T.; et al.
Abstract : Background: Systemic lupus erythematosus (SLE) affects predominantly women of reproductive age. However, in about 15% of patients SLE begins before the age of 18 years (early-onset) and in 10-20% of patients SLE is first diagnosed after the age of 50 years (late-onset). The age at disease onset significantly impacts on clinical presentation, disease course, response to treatment and prognosis. Objectives: To compare demographic, clinical features and disease outcome between patients with early-onset and those with late-onset SLE and to determine whether patients' age affects the time interval until diagnosis. Methods: All SLE patients from the Portuguese registry Reuma.pt/LES with disease onset at age≤18 years-old or at age≥50 years-old were included. Patients' data were cross-sectionally analyzed upon records from the last visit. The differences between groups with early and late onset were determined by Student t-tests, chi-square or Fisher's exact tests. Results: 313 SLE patients were included (157 early-onset; 156 late-onset). In the early-onset group, 88% were women, mean disease duration 16.8±10.5y and mean age of diagnosis 17±5.9y. Higher education level was noted in the younger group. 81.6% of patients with late-onset SLE were women, mean disease duration 9.37±5.2y and mean age of diagnosis 60.5±7.5y. Photosensitivity, arthritis and neurological disorder were statistically more prevalent in the late-onset group. Anti-Sm positivity was observed more frequently in early-onset SLE. Co-morbidities were also more common in this age group. Disease activity evaluated using the SLEDAI-2K was higher in the early-onset (3.0±3.3 vs 2.0±2.8; p=0.01) while accumulated damage was higher in the older age group (1.0±1.3 vs 0.69±1.4; p<0.001). Diagnosis delay was significantly greater in patients with early-onset than in the late-onset group (3.1±5 vs 1.7±3 y; p=0.001). Conclusions: Patients with late-onset SLE have more co-morbid conditions and greater accumulated damage despite shorter disease duration and lower disease activity. Age of onset has a significant impact not only on the clinical characteristics and disease outcome, but also on time until diagnosis. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.5306